2019
DOI: 10.3390/cancers11040512
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Identity: HOX Genes in Normal and Cancer Stem Cells

Abstract: Stem cells are undifferentiated cells that have the unique ability to self-renew and differentiate into many different cell types. Their function is controlled by core gene networks whose misregulation can result in aberrant stem cell function and defects of regeneration or neoplasia. HOX genes are master regulators of cell identity and cell fate during embryonic development. They play a crucial role in embryonic stem cell differentiation into specific lineages and their expression is maintained in adult stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 106 publications
(124 reference statements)
0
30
1
Order By: Relevance
“…[43][44][45] The characteristic embryonic HOX gene expression profiles, the so-called "HOX code," is sustained in adults, where HOX genes regulate cell specification and tissue differentiation according to the body region. 46 Accordingly, the topographical specificity of HOX genes is maintained in tissue-typical MSCs and further on after differentiation, which indicates that HOX genes are decisive for the specification of MSC identity. As HOX gene expression profiles mirrors that of the developmental origin of MSCs, HOX gene expression can be used to distinguish different stem cell populations and in particular MSCs of functionally distinct tissues.…”
Section: Potential Interactions Of Lr-mscs and Lung Cancer Cellsmentioning
confidence: 99%
“…[43][44][45] The characteristic embryonic HOX gene expression profiles, the so-called "HOX code," is sustained in adults, where HOX genes regulate cell specification and tissue differentiation according to the body region. 46 Accordingly, the topographical specificity of HOX genes is maintained in tissue-typical MSCs and further on after differentiation, which indicates that HOX genes are decisive for the specification of MSC identity. As HOX gene expression profiles mirrors that of the developmental origin of MSCs, HOX gene expression can be used to distinguish different stem cell populations and in particular MSCs of functionally distinct tissues.…”
Section: Potential Interactions Of Lr-mscs and Lung Cancer Cellsmentioning
confidence: 99%
“…The study by Faiella et al (1994) also first demonstrated the PI Hox-Hox interaction. Recent pubications (Seifert et al, 2015; Smith et al, 2019) have emphasized that Hox genes are important in regulating ES stem cell directionality. The cells involved in the embryo clearly include pluripotent stem cells too.…”
Section: Discussion: Best Guess Hypothesis and Future Prospects How mentioning
confidence: 99%
“…Multiple reports have demonstrated that mis-regulation of HOX genes expression plays key roles in the development of cancers. Only in the last five years have more than 50 reviews related to this subject been published; see, for example, References [4,[8][9][10][11]. However, such studies were typically based on different technologies used in different labs and analyzed by different computational tools.…”
Section: Introductionmentioning
confidence: 99%